The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.21577/0103-5053.20190165
|View full text |Cite
|
Sign up to set email alerts
|

New Limonoids from Dictyoloma vandellianum and Sohnreyia excelsa: Chemosystematic Considerations

Abstract: Molecular phylogenetic studies separated and united a group of genera that constituted the Spathelia-Ptaeroxylon clade, in which Dictyoloma and Sohnreyia have been included. Our taxonomic interest in the Dictyoloma vandellianum and Sohnreyia excelsa stimulated an investigation of both species searching for limonoids. Leaves from D. vandellianum afforded the new limonoid 1,2-dihydro-1α-hydroxy-8,30-epoxy-cneorin R, and heartwood yielded the new rearranged limonoid dictyolomin. Leaves from S. excelsa afforded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The chief sources of limonoids are the Meliaceae and Rutaceae plant families (Da Silva et al 1984; Fig. 1 Basic limonoid skeleton Champagne et al 1992;Roy and Saraf 2006;Liao et al 2009;Fang et al 2011;Sun et al 2018;Sartor et al 2019;Cui et al 2021;Luo et al 2022) but they also can be found very occasionally in Cneoracea and Ptaeroxylaceae families and Harrisonia spp. of Simaroubaceae (Ourison et al 1964;Connolly 1983;Da Silva et al 1987;Tundis et al 2014;Amit and Shailendra 2006;Tan and Luo 2011).…”
Section: Natural Sources Of Degraded Limonoidsmentioning
confidence: 99%
“…The chief sources of limonoids are the Meliaceae and Rutaceae plant families (Da Silva et al 1984; Fig. 1 Basic limonoid skeleton Champagne et al 1992;Roy and Saraf 2006;Liao et al 2009;Fang et al 2011;Sun et al 2018;Sartor et al 2019;Cui et al 2021;Luo et al 2022) but they also can be found very occasionally in Cneoracea and Ptaeroxylaceae families and Harrisonia spp. of Simaroubaceae (Ourison et al 1964;Connolly 1983;Da Silva et al 1987;Tundis et al 2014;Amit and Shailendra 2006;Tan and Luo 2011).…”
Section: Natural Sources Of Degraded Limonoidsmentioning
confidence: 99%